(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the pattern of major congenital malformations in neonates admitted in Nishtar Hospital Multan and evaluate their early outcome. Study Design: Descriptive study. Place and Duration of Study: This study was conducted at the Department of Anatomy, in collaboration with department of Gynaecology & Obstetrics and department of Paediatrics Nishtar Medical Institution Multan from March to August 2012. Materials and Methods: A total of 431 neonates were admitted in Paediatric Wards including those referred from outside and from Labour Room of Nishtar Hospital. Children with major congenital malformations were identified by clinical examination and confirmed by appropriate radio-diagnostic methods. These neonates were immediately referred to the surgical team for intervention. Results: A total of 57 neonates with congenital malformations were admitted during the study period. Thirty one were males and 26 females. Fetal anomalies were diagnosed correctly in 17 cases out of a total of 19 inborn deliveries on maternal ultrasound while it was missed in one fetus and incorrectly diagnosed in one case. A total of 48 patients had surgery out of which 4 (8.3%) died in the neonatal period. Five cases were booked for elective surgery beyond the neonatal period. Out of 4 neonates with congenital heart disease one case was referred outside, one neonate died preoperatively while 2 infants were managed conservatively. Conclusion: Due to detection of fetal anomalies, early surgical intervention, and intensive neonatal care, most infants can be rescued after a successful primary operation.